2011
DOI: 10.1093/ejechocard/jeq194
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mitral valve area by pressure half-time and proximal isovelocity surface area method in patients with mitral stenosis: effect of net atrioventricular compliance

Abstract: MVA calculated with both the PISA and PHT methods correlated well with MVA calculated with the planimetry method. However, the PISA rather than PHT is recommended for patients with MS and extreme C(n) values because PISA, unlike PHT, is not affected by changes in C(n).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Pressure half time is routinely utilized to calculate the MVA and has level 1 recommendation for assessment for severity of MS . PHT is dependent on left atrial and left ventricular compliance and can be inaccurate in patients with abnormal compliance . The routinely used equation for MVA (MVA = 220/PHT) as proposed by Hatle et al also has potential pitfalls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure half time is routinely utilized to calculate the MVA and has level 1 recommendation for assessment for severity of MS . PHT is dependent on left atrial and left ventricular compliance and can be inaccurate in patients with abnormal compliance . The routinely used equation for MVA (MVA = 220/PHT) as proposed by Hatle et al also has potential pitfalls.…”
Section: Discussionmentioning
confidence: 99%
“…The numerator in the equation “220” is derived from the equation 11.6 × Cn × delta P½. Cn is net atrioventricular compliance, and the assessment of Cn has been described previously . In these studies, it was observed that for patients with abnormal (increased and decreased) atrioventricular compliance (Cn) the correlation of the MVA with PISA method or planimetery was not as good as patients with normal compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also indicated that C n contributes to determining pulmonary hypertension in MS, 3, 1214, 17, 25, 29 but had several limitations. Li et al 10 could not find any relation between parameters of MS severity and pulmonary pressure from the small number of patients studied.…”
Section: Discussionmentioning
confidence: 99%
“…C n was determined noninvasively by means of Doppler echocardiography as previously described 9, 12, 14, 17, 25 : C n (mL/mmHg) = 1270 × (planimetric MV area [cm 2 ]/E-wave downslope [cm/s 2 ]). In those patients with nonlinear diastolic flow, the mid-diastolic flow was used, which is felt to best represent the valve stenosis as opposed to early LA depressurization, and the slope was extrapolated back to obtain the initial maximal velocity.…”
Section: Methodsmentioning
confidence: 99%
“…16 Being independent of reference valve flow, PISA is not affected by significant MR or AR. Loading conditions also are less likely to influence the calculations because the acquisition of all formula components can be accomplished in a couple of beats.…”
Section: Quantitative Assessmentmentioning
confidence: 93%